Les mots et les images. Ambiguity and Disorientation in Language (diségno, 2025)
In 1929, René Magritte published Les mots et les images in the magazine La Révolution surréaliste, a series of eighteen illustrations that offered a conceptual experiment on the relationship between text and image. [read more]